Spatial variability of physical attributes of soil under different use and management conditions - Cavalcante, Eloiza G. S. [UNESP]; Alves, Marlene C. [UNESP]; de Souza, Zigomar M.; Pereira, Gener T. [UNESP] (FapUNIFESP (SciELO), 2011)
The soil tillage and the vegetable species have expressive effect on spatial variability of soil. The objective of this work was to study the spatial variability of some physical attributes of savannah soil (Oxisol) of Mato Grosso do Sul, Brazil, under different management. The soil samples were collected in a grid, with regular intervals of 2.0 m, total of 64 points, in the depths of 0-0.10 m and 0.10-0.20 m for bulk density and in the depths 0-0.15 m; 0.15-0.30 m; 0.30-0.45 m and 0.45-0.60 m for the soil resistance to the penetration and soil water content, in the areas with native vegetation (savannah), no-tillage, conventional system and pasture. The greatest variability measured through the variation coefficient and nugget effect was observed for the soil resistance to penetration. The no-tillage showed major range when compared to native vegetation, conventional system and pasture. The uses and managements induce, in the crescent order of no-tillage, conventional system and pasture towards degradation of soil physical attributes in relation to native vegetation.
Variabilidade espacial de atributos físicos do solo sob diferentes usos e manejos
Keywords: Agroecosystems; Geostatistics; Soil tillage; Spatial dependence